2000
DOI: 10.1300/j067v20n01_11
|View full text |Cite
|
Sign up to set email alerts
|

The NonMSW Task Supervisor, MSW Field Instructor, and the Practicum Student

Abstract: This paper adds to the literature on field instruction and supervision of social work practicum students by nonMSW professionals. It shares insights gained from a focus group discussion of professionals' experiences with practica when there was no MSW on site.Reported findings indicate student, agency, and relational characteristics contribute to the success of these placements. The focus group and the authors conclude that active involvement of all three parties--the on-site nonMSW supervisor, the off-site MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Henderson (2010) found that in placements with off-site supervision the liaison persons mainly communicated with the off-site supervisors, giving less attention to the work-based supervisors. Other research exploring off-site supervision in social work placement, highlighted the importance of triad relationship and communication between the off-site supervisors, work-based supervisor and the student (Abram, Hartung, & Wernet, 2000); this USA based research did not refer to the liaison role or experience. Alston (2007) recognises that in rural and remote areas liaison persons are often involved in supporting placements with off-site supervision, as fewer social work qualified professionals work in organisations in those communities.…”
Section: The Liaison Person and Off-site Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Henderson (2010) found that in placements with off-site supervision the liaison persons mainly communicated with the off-site supervisors, giving less attention to the work-based supervisors. Other research exploring off-site supervision in social work placement, highlighted the importance of triad relationship and communication between the off-site supervisors, work-based supervisor and the student (Abram, Hartung, & Wernet, 2000); this USA based research did not refer to the liaison role or experience. Alston (2007) recognises that in rural and remote areas liaison persons are often involved in supporting placements with off-site supervision, as fewer social work qualified professionals work in organisations in those communities.…”
Section: The Liaison Person and Off-site Supervisionmentioning
confidence: 99%
“…The limited literature available about field education with off-site supervision highlights the importance of the triad relationship (Abram, et al, 2000), the support needed for field educators, work-based supervisors and students (Clare, 2001;Henderson, 2010), the need to clarify the responsibilities of the supervisors (Karban, 1999) and the potential for power imbalances between the on-site and off-site supervisors (Henderson, 2010). There are concerns raised about the students' learning in placements supported by an off-site supervisor, for example, about their experiences, learning and assessment and whether the lack of clearly defined social work roles adversely affects the development of social work identity (Plath, 2003).…”
Section: Learning In Field Education With Off-site Supervisionmentioning
confidence: 99%
“…Organisations and supervisors may focus on constraints and efficiencies, limiting the placement opportunities they in turn offer to students (Barton et al, 2005).Those social workers supporting field education face heavy workloads as they combine their responsibilities as practice educators and as employees (Moriarty et al, 2009). Providing placement opportunities for social work students with social work qualified supervisors on site is therefore becoming more difficult (Abram et al, 2000;Barton et al, 2005).…”
Section: Field Educationmentioning
confidence: 99%
“…Challenges to individual supervision include: (a) concerns that individual supervision style may cause undue dependency and discourage risk-taking (Marshack & Glassman, 1991), (b) changes in practice, leaving less time for Downloaded by [Umeå University Library] at 15:53 17 November 2014 supervision and higher expectations of students, and (c) the need to expose students to a broader array of practice areas, settings, and supervisory styles (Jarmon-Rohde, McFall, Kolar, & Strom, 1997). More recently, suggestions for new models of field education have included many alternatives to the one-on-one supervision model, such as rotations (Grossman, 1991;Reisch & Jarmon-Rohde, 2000;Spitzer et al, 2001), community-based field instruction (Reisch & Jarmon-Rohde, 2000), group field instruction (Globerman & Bogo, 2003;Kaplin, 1991;Marshack & Glassman, 1991;Reisch & Jarmon-Rohde, 2000), sharing/co-supervision (Abram, Hartung, & Wernet, 2000;Coulton & Krimmer, 2005), and others. As described in the following, the efforts of the national Hartford Partnership Program for Aging Education (HPPAE) have influenced social work curricula in myriad ways, including the increased use of rotation models of field education in programs across the country.…”
Section: Models Of Field Educationmentioning
confidence: 99%